Processes for Preparing Peroxynitrite Electrosensitive Depositions and Methods of Selective Detection for Further Biostimulant Screening - Ioana Silvia Hosu; Anda Maria Baroi; Roxana Ioana Matei (Brazdis); Toma Fistos (Proceedings, 2023)
As biostimulants may have a mechanism related to increasing tolerance to abiotic stress (drought, salinity, heat shock, etc., which will increase the production of Reactive Oxygen Species, ROS, such as peroxynitrite (PON)), this work proposes electrochemical solutions for the rapid screening of biostimulants, based on a sensor’s selectivity toward PON, for further efficient biostimulant formulation, as nowadays, biostimulants are still developed and commercialized using compositions developed by hazard, and not by design (as this work proposes).